The effect of boron on oxide scale formation in a new polycrystalline superalloy - Kontis, P; Pedrazzini, S; Gong, Y; Bagot, P; Moody, M; Reed, R (Elsevier, 2016)
Boron addition to a new polycrystalline nickel-based superalloy promotes the formation of a hitherto unreported aluminoborate phase, in the scale produced by oxidation in air at 900 °C for ~ 10,000 h. Atom probe tomography provides unambiguous confirmation of this. The ramifications of its formation are discussed.